Social Cognition in The Reconstruction of Corruption News Discourse on Private Television SCTV and INews TV - Hananta, Rakhmat Dwi; Mardikantoro, Hari Bakti (Pascasarjana Universitas Negeri Semarang, 2019)
The study of discourse analysis is not based solely on aspects of text analysis, but rather on how text is produced. Therefore, we need a study of the representation of social cognition. This study aimed to interpret the social cognition level in SCTV and INews TV journalists in reconstructing corruption news discourse. The method used in this study is the listening and talking.The simak method includes the technique ofuninvolved conversation observation (simak bebas libat cakap), recording, and note-taking techniques. The cakap method include triggering (pancing), at will conversation (cakap semuka), and recording and note-taking techniques. The analysis technique used in this study was Critical Discourse Analysis technique proposed by Teun A. van Dijk. The results showed that in reconstructing corruption news discourse, SCTV and iNews Tv usedperson scheme, self-scheme, role scheme, and event scheme. The use of these schemes was to support news broadcasted values. The journalists in the level of social cognition from each television both SCTV and INews TV play a role as communicator of the part of society which always informs the dominant discourse that develops in society. The benefits of this research are for the development of discourse science as well as reference material for the community in understanding the characteristics of a media.